Anterior Capsulolabral Allograft Reconstruction for Revision Multidirectional Instability Surgery - Mitchell S. Mologne, B.S.; Peter S. Chang, M.D.; Caleb S. Davis, B.S.; Alexander R. Garcia, B.S.; Annabel R. Geissbuhler, B.S.; Matthew L. Vopat, M.D.; John M. Apostolakos, M.D., M.P.H.; Peter J. Millett, M.D., M.Sc. (Arthroscopy Techniques, 2025)
Multidirectional instability (MDI) can be a challenging condition, with patients often experiencing recurrent dislocation and subluxation events along with debilitating shoulder pain. Although many cases of MDI can be resolved with nonoperative treatment/prolonged physical therapy, some patients progress to surgical management. Primary surgical management of MDI has displayed suboptimal results, with up to one fourth of patients experiencing recurrent instability postoperatively, necessitating revision surgery. The purpose of this Technical Note is to describe anterior capsulolabral reconstruction using a soft-tissue allograft, for patients with multidirectional instability who have not responded to other stabilization procedures. This technique can be a reproducible way to improve shoulder stability and obtain good postoperative outcome measures for patients with recurrent MDI.